2010
DOI: 10.1038/ki.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

The retinitis pigmentosa GTPase regulator interacting protein 1 (RPGRIP1) links RPGR to the nephronophthisis protein network

Abstract: Nephronophthisis is a heterogenetic autosomal recessive disorder associated with multiple developmental abnormalities, including cystic kidney disease and retinal degeneration. Retinal dystrophies, in particular the X-linked forms, are believed to represent a distinct group of hereditary diseases; however, their genetic complexity and overlap with other syndromic diseases is increasingly apparent. In this study, we report that depletion of retinitis pigmentosa GTPase regulator (RPGR) during zebrafish embryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…For example, the centriolar satellite protein SSX2IP targets Cep290 to the TZ (Klinger et al , ). Moreover, Rpgrip1 directly interacts with Nphp4 and with Cep290 (Roepman et al , ; Gerner et al , ) making it plausible that Rpgrip1 is able to take part in the localisation of proteins to the TZ. Remarkably, photoreceptor cilia of Rpgrip1 nmf247 / nmf247 mice lack Nphp4 (Patil et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the centriolar satellite protein SSX2IP targets Cep290 to the TZ (Klinger et al , ). Moreover, Rpgrip1 directly interacts with Nphp4 and with Cep290 (Roepman et al , ; Gerner et al , ) making it plausible that Rpgrip1 is able to take part in the localisation of proteins to the TZ. Remarkably, photoreceptor cilia of Rpgrip1 nmf247 / nmf247 mice lack Nphp4 (Patil et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Since only eye defects are described in mice and humans suffering from mutations in RPGRIP1 , most studies focussed on the relationship between Rpgrip1 and eye development. Nevertheless, it was previously suggested that Rpgrip1 is not only important for eye development but also contributes to the development of the kidneys (Roepman et al , ; Gerner et al , ). Our data confirm this hypothesis and go one step further indicating that Rpgrip1 participates at least in the development of the kidneys, the brain and the heart (Fig A–C).…”
Section: Discussionmentioning
confidence: 99%
“…A CEP290 hypomorphic allele enhances the severity of retinal degeneration caused by RPGR loss in the mouse (Rao et al, 2016). Likewise, CEP290 and RPGR interact genetically in zebrafish (Gerner et al, 2010). Also in the mouse, CEP290 null phenotypes were exacerbated by the loss of MKKS/BBS6, a chaperone required for BBSome assembly.…”
Section: Genetic Interactions Governing Tz Assembly and Functionmentioning
confidence: 99%
“…NPHP5, calmodulin, and RP GTPase regulator coprecipitate, probably as a multi‐protein complex (6, 18). NPHP5 interacts with RP GTPase regulator indirectly (19, 20) and with CEP290/ NPHP6 directly (21, 22). In vitro studies showed that CEP290‐NPHP5 interaction is required for ciliogenesis (8).…”
mentioning
confidence: 99%